2011
DOI: 10.1016/j.jsg.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Fault architecture and deformation processes within poorly lithified rift sediments, Central Greece

Abstract: a b s t r a c tDeformation mechanisms and resultant fault architecture are primary controls on the permeability of faults in poorly lithified sediments. We characterise fault architecture using outcrop studies, hand samples, thin sections and grain-size data from a minor (1e10 m displacement) normal-fault array exposed within Gulf of Corinth rift sediments, Central Greece. These faults are dominated by mixed zones with poorly developed fault cores and damage zones. In poorly lithified sediment deformation is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…A foliated-clay structure developed in most of the clay-rich fault core. Loveless et al, 2011) have noted the presence of mixed zones along faults in poorly consolidated sediments. These studies are in poorly consolidated siliciclastic units with grain size ranging from gravel to clay that underwent deformation through particulate flow at less than 1 km depth.…”
Section: Fault Growth and Clay Smearingmentioning
confidence: 99%
See 1 more Smart Citation
“…A foliated-clay structure developed in most of the clay-rich fault core. Loveless et al, 2011) have noted the presence of mixed zones along faults in poorly consolidated sediments. These studies are in poorly consolidated siliciclastic units with grain size ranging from gravel to clay that underwent deformation through particulate flow at less than 1 km depth.…”
Section: Fault Growth and Clay Smearingmentioning
confidence: 99%
“…Heynekamp et al (1999); Sigda et al (1999); Rawling et al (2001) and Rawling and Goodwin (2003) defined the mixed zone as being located between the fault core and the damage zone rather than being the fault core. Loveless et al (2011) considers the mixed zone as representing the fault core based on hydrological behaviour. Due to this ambiguity in the meaning of the term mixed zone, we prefer to use the term breccia as a geometrical description of the sandy pods texture.…”
Section: Fault Growth and Clay Smearingmentioning
confidence: 99%
“…Increased tortuosity between holes further reduces fluid flux across the fault, but this flux is still greater than that across a thin clay smear. Sand smears separating two or more parallel clay smears in a single fault are described by several authors [ Loveless et al ., ; Bastesen et al ., ; Bense et al ., ; Kristensen et al ., ; Kettermann et al ., ], but confident observation of permeable connectivity across the fault is difficult in a field setting.…”
Section: Discussionmentioning
confidence: 98%
“…Outcrop studies provide high‐resolution data of clay smear structures and processes in a wide range of spatial scales and lithification states [ Weber et al ., ; Lindsay et al ., ; Lehner and Pilaar , ; Foxford et al ., ; Heynekamp et al ., ; Aydin and Eyal , ; Bense et al ., ; van der Zee et al ., ; Clausen et al ., ; Doughty , ; van der Zee and Urai , ; Davatzes and Aydin , ; Eichhubl et al ., ; Faerseth , ; Loveless et al ., ; Kristensen et al ., ; Kettermann et al ., ]. The inherent 3‐D variability of clay smears is recognized as difficult to explore in two‐dimensional outcrop studies [ Foxford et al ., ; Vrolijk et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…In regard to a 559 mechanically layered sequence of beds, the resultant distribution of faults or joints 560 has higher complexity (e.g., Welch et al, 2009b). The detailed outcrop studies also 561 suggested that stratigraphy plays an important role in determining the detailed fault 562 architecture at meso-scale and micro-scale (e.g., Loveless et al, 2011;Pei et al, 563 2015). Many mechanical and physical models suggested the important role of 564 stratigraphy and its strength in controlling the deformation style; however, it is likely 565 to be second-order controls superimposed upon the first-order geometry that are 566 dominated by the throw distribution along a thrust fault (Allmendinger, 1998;Dixon, 567 2004;Pei et al, 2014;Welch et al, 2009a).…”
mentioning
confidence: 99%